The L^P-spaces of functions from the n-dimensional real space to the N-dimensional quaternionic space - Abugirda, Hussien A. H.; Abdullah, Mohammed Kh.; Al-Yasiri, Khaldoun S. (Iraqi Journal of Science, 2024)
In this paper, we introduce new definitions of the - spaces  namely the    - spaces  Here,  and  are natural numbers that are not necessarily equal, such that . The space  refers to the n-dimensional Euclidean space,  refers to the quaternions set and  refers to the N-dimensional quaternionic space. Furthermore, we establish and prove some properties of their elements. These elements are quaternion-valued N-vector functions defined on , and the  spaces  have never been introduced in this way before.